Coffee Shop as a Space for Learning English Speaking Skills for Underprivileged Students - Authar, Nailul; Saputri, Tiyas; Djuwari, Djuwari; Fitriyah, Fifi Khoirul (UKInstitute, 2022)
Take a look at from the current situation, drinking a cup of coffee in a coffee shop becomes a living style trend in society. Not only teenagers experience enjoyable and comfort there, but also adult people feel the same too. This phenomenon are happening right now. Seeing this situation, it would be better if the activity of drinking coffee that was liked by the general public could be a way to overcome boredom in learning English, especially in speaking skills. However, not all students can get these facilities due to economic factors. They are called